A metal-free heterogeneous photocatalyst for the selective oxidative cleavage of CC bonds in aryl olefins via harvesting direct solar energy. Issue 14 (22nd June 2020) - Zhang, Yu; Hatami, Nareh; Lange, Niklas Simon; Ronge, Emanuel; Schilling, Waldemar; Jooss, Christian; Das, Shoubhik
Abstract : A mild protocol has been developed using polymeric carbon nitrides (PCN) as metal-free heterogeneous photocatalyst to convert olefins into the corresponding carbonyls which even can be applied in the gram scale synthesis using direct solar energy. Abstract : Selective cleavage of CC bonds is highly important for the synthesis of carbonyl containing fine chemicals and pharmaceuticals. Novel methodologies such as ozonolysis reactions, Lemieux–Johnson oxidation reaction etc . already exist. Parallel to these, catalytic methods using homogeneous catalysts also have been discovered. Considering the various advantages of heterogeneous catalysts such as recyclability and stability, couple of transition metal-based heterogeneous catalysts have been applied for this reaction. However, the pharmaceutical industries prefer to use metal-free catalysts (especially transition metal-free) to avoid further leaching in the final products. This is for sure a big challenge to an organic chemist and to the pharmaceutical industries! To make this feasible, a mild and efficient protocol has been developed using polymeric carbon nitrides (PCN) as metal-free heterogeneous photocatalysts to convert various olefins into the corresponding carbonyls. Later, this catalyst has been applied in the gram scale synthesis of pharmaceutical drugs using direct solar energy. Detailed mechanistic studies revealed the actual role of oxygen, the catalyst, and the light source.